2022
DOI: 10.7759/cureus.30045
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Use of Impella Device in Cardiogenic Shock: A Systematic Review

Abstract: Impella (Abiomed, Danvers, MA) devices nowadays have been linked to cardiogenic shock (CS) due to the importance of their use as therapeutic instruments. This study aims to review pathophysiologic mechanisms of cardiogenic shock and the implementation of Impella to overcome this condition. To investigate several different types of studies and analyze the use of Impella device in cardiogenic shock and the outcomes of heart malfunctioning and determine its positive and negative impacts as a therapeutic tool in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
3
0
3
Order By: Relevance
“…Una serie de revisiones sistemáticas se han centrado en evaluar los efectos del dispositivo Impella CP* en la reducción de la mortalidad y desenlaces clínicos de los pacientes 2,4,5 . Dichas revisiones han mostrado que la mayoría de estudios evaluando el dispositivo Impella son estudios retrospectivos con muestras relativamente pequeñas 2 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Una serie de revisiones sistemáticas se han centrado en evaluar los efectos del dispositivo Impella CP* en la reducción de la mortalidad y desenlaces clínicos de los pacientes 2,4,5 . Dichas revisiones han mostrado que la mayoría de estudios evaluando el dispositivo Impella son estudios retrospectivos con muestras relativamente pequeñas 2 .…”
Section: Discussionunclassified
“…3 El dispositivo mejora la presión arterial, descomprime el ventrículo izquierdo disminuyendo su trabajo, aumenta la frecuencia cardíaca y está asociado a una baja tasa de eventos adversos. 4 En Latino América, existen pocos estudios evaluando la eficacia de los dispositivos de soporte circulatorio mecánico. En el caso de Chile, no existen estudios eva-…”
Section: Introductionunclassified
“…Different models are available depending on the supply they provide: Impella 2.5 (2.5 L/min flow), Impella CP (4 L/min flow), and Impella 5.0 (5 L/min flow) [ 8 ]. A recent systematic review conducted by Munoz et al demonstrated the efficacy of the Impella device in improving survival in cardiogenic shock despite the etiology [ 9 ]. Moreover, this device has been demonstrated to increase coronary microcirculation while lowering the workload burden in the left ventricle [ 9 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
“…A recent systematic review conducted by Munoz et al demonstrated the efficacy of the Impella device in improving survival in cardiogenic shock despite the etiology [ 9 ]. Moreover, this device has been demonstrated to increase coronary microcirculation while lowering the workload burden in the left ventricle [ 9 ]. When comparing the management of the Impella device with IABP in acute myocardial infarction-related cardiogenic shock, the Impella device showed better outcomes, as there was a lower amount of troponins and creatine phosphokinase when using the Impella device [ 73 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
See 1 more Smart Citation